1996
DOI: 10.1007/s004240050029
|View full text |Cite
|
Sign up to set email alerts
|

Myosin heavy chain isoform transformation in single fibres from m. vastus lateralis in spinal cord injured individuals: effects of long-term functional electrical stimulation (FES)

Abstract: The myosin heavy chain (MHC) composition of single fibres from m. vastus lateralis of five spinal- cord-injured (SCI) individuals was analysed by Sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) before, and after 6 and 12 months of functional electrical stimulation (FES)-training, administrated for 30 min three times per week. Prior to FES training 37.2% of the fibres contained only MHC IIB, 21.2% only MHC IIA, and 40.7% co-expressed MHC IIA and MHC IIB. After 6 months of FES-training the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
81
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 0 publications
10
81
1
Order By: Relevance
“…This supports previous observations, that adaptation in these parameters is somewhat more prolonged compared with the rise in muscle enzyme activity (Blomqvist and Saltin 1983;Henriksson 1977), and that the activity of CS does not limit _ V O 2max (Rasmussen and Rasmussen 2000). In a separate part of the present study, the determination of myosin heavy chain (MHC) isoforms over a 12 month period revealed a shift from MHC IIx to MHC IIa isoform expression, thus indicating more oxidative phenotype characteristics (Andersen et al 1996). However, the ®bre-type shift occurred continuously over the 12 month training period, despite the present demonstration of a levelling-o in the change of the muscle enzyme activity after 3 months.…”
Section: Discussionsupporting
confidence: 92%
“…This supports previous observations, that adaptation in these parameters is somewhat more prolonged compared with the rise in muscle enzyme activity (Blomqvist and Saltin 1983;Henriksson 1977), and that the activity of CS does not limit _ V O 2max (Rasmussen and Rasmussen 2000). In a separate part of the present study, the determination of myosin heavy chain (MHC) isoforms over a 12 month period revealed a shift from MHC IIx to MHC IIa isoform expression, thus indicating more oxidative phenotype characteristics (Andersen et al 1996). However, the ®bre-type shift occurred continuously over the 12 month training period, despite the present demonstration of a levelling-o in the change of the muscle enzyme activity after 3 months.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Wbres containing MHC IIA isoforms have been found to appear in the human skeletal muscle with an enzyme proWle and a speed of contraction that make these Wbres more adapted for strength performance than Wbres containing MHC I isoforms (Larsson and Moss 1993). Large percentages of histochemically type IIX Wbres and MHC IIX isoforms have been observed in obese females (Mandroukas et al 1984) and in spinal cord injured individuals (Andersen et al 1996).…”
Section: Discussionmentioning
confidence: 96%
“…Electrical stimulation has been previously reported to increase ®ber cross-sectional area (Neumayer et al 1997), increase the proportion of type I ®bers (Munsat et al 1976;Henricksson et al 1982), increase the percentage of MHC IIa (Andersen et al 1996) and increase oxidative enzyme activity (Martin et al 1992) within the electrically stimulated muscles. In one pilot study, the 19% reduction in ®ber cross-sectional area seen in the quadriceps femoris muscle after 46 weeks of injury was reversed, with a 20% increase in total ®ber cross-sectional area noted after 8 weeks of electrical stimulation-induced resistance training ).…”
Section: Introductionmentioning
confidence: 94%
“…In many studies, the eects of electrical stimulation on skeletal muscle have been analyzed, although these studies have almost exclusively investigated electrical stimulation training on the muscle characteristics in humans with a chronic spinal-cord injury (greater than 6 months post injury: Munsat et al 1976;Henricksson et al 1982;Martin et al 1992;Andersen et al 1996;Neumayer et al 1997). Electrical stimulation has been previously reported to increase ®ber cross-sectional area (Neumayer et al 1997), increase the proportion of type I ®bers (Munsat et al 1976;Henricksson et al 1982), increase the percentage of MHC IIa (Andersen et al 1996) and increase oxidative enzyme activity (Martin et al 1992) within the electrically stimulated muscles.…”
Section: Introductionmentioning
confidence: 99%